PENGARUH VARIASI LATIHAN LADDER DRILL TERHADAP KELINCAHAN ATLET PUTRA HOCKEY UNIMED CLUB TAHUN 2023 - Samuel Aritonang, Andrian; Siahaan, David (JURNAL ILMU KEOLAHRAGAAN, 2024)
This study aims to determine the effect of variations in ladder drill training on the agility of Unimed Hockey Club male athletes in 2023. There are five variations of training forms, where the five variations of training forms are designed to increase athletes' agility. This research was carried out at the Unimed multipurpose field on Jln William Iskandar Pasar V which is located on the campus of Medan State University, North Sumatra. The research was carried out in March-May 2024. The research method used in this research was an experimental method by providing treatment to the sample in the form of an exercise program. The population in this study was 18 people. The total sample of 10 people was obtained using a purposive random sampling technique where the sample was divided into two groups using the ordinal pairing method. This research instrument is to collect data using tests and measurements, namely the zig-zag run test. The research was carried out for six weeks with training three times a week. Statistical calculations use a paired t-test, based on the analysis requirements test, it is found that the two data are normally distributed samples and come from a homogeneous population, so both data can be calculated by the t-test to obtain hypotheses. Based on the t-test calculations, the t-test value obtained for the difference between the pre-test and the post-test for variations of the ladder drill exercise on the agility of Unimed Hockey Club male athletes in 2023 is tcount = 6.28. Next, it will be compared with the ttable value with a level of α = 0.05 with dk = n-1 = 10-1 = 9, obtained 2.58, then tscore = 7.05> tstandat = 2.58. So it can be concluded that there is an influence of variations in ladder drill training on the agility of Unimed Hockey Club male athletes in 2023